Racial integration : a social intervention on a South African university campus - Kim, Caroline (Department of Psychology, 2016)
Gordon Allport's contact theory has given rise to the widely accepted proposition that contact improves intergroup attitudes, with stronger effects in settings that reflect optimal conditions of contact. Investigators have long been interested in the effects of contact in South Africa where, until twenty years ago, intergroup contact had been formally restricted. Although research has shown a significant inverse relationship between contact and prejudice in this country, 'hyper-segregation' has been well documented in everyday spaces where diverse groups of people coexist. Of significance, these patterns of racial isolation are also prevalent in contexts where contact conditions are among the most optimal: university campuses. Despite the hope that naturally occurring encounters between different groups would start to create more integrated environments, it may be that interventions would be required to facilitate the direct interpersonal contact presupposed in contact theory. This thesis presents data from two sets of longitudinal studies conducted in university dining halls to investigate whether patterns of 'self-segregation' could be disrupted. The interventions enhanced optimal conditions, and addressed intergroup anxiety - one of the main hindrances to intergroup contact in diverse spaces on this campus - by attempting to instill positive emotions. Both naturalistic observational methods and quasi-experimental methods were used to measure changes in intergroup attitudes and behaviors as a function of the interventions. Students' seating patterns in the dining hall were mapped before, during, and after the intervention. The impact of the intervention on intergroup contact, cross-group friendship, intergroup anxiety, and social distance were measured through pretest-posttest surveys. Based on evidence from the first set of studies, a larger-scale version of the intervention was launched in the same format, one year later.